Comparison of 68Ga-FAPI and 18F-FDG PET/CT for the diagnosis of primary and metastatic lesions in abdominal and pelvic malignancies: A systematic review and meta-analysis - Liu, Xue; Liu, Huiting; Gao, Cailiang; Zeng, Wenbing (Frontiers in Oncology, 2023)
Purpose The purpose of this study is to compare the application value of 68Ga-FAPI and 18F-FDG PET/CT in primary and metastatic lesions of abdominal and pelvic malignancies (APMs). Materials The search, limited to the earliest available date of indexing through 31 July 2022, was performed on PubMed, Embase, and Cochrane Library databases using a data-specific Boolean logic search strategy. We calculated the detection rate (DR) of 68Ga-FAPI and 18F-FDG PET/CT in the primary staging and recurrence of APMs, and pooled sensitivities/specificities based on lymph nodes or distant metastases. Results We analyzed 473 patients and 2775 lesions in the 13 studies. The DRs of 68Ga-FAPI and 18F-FDG PET/CT in evaluating the primary staging and recurrence of APMs were 0.98 (95% CI: 0.95-1.00), 0.76 (95% CI: 0.63-0.87), and 0.91(95% CI: 0.61-1.00), 0.56 (95% CI: 0.44-0.68), respectively. The DRs of 68Ga-FAPI and 18F-FDG PET/CT in primary gastric cancer and liver cancer were 0.99 (95% CI: 0.96-1.00), 0.97 (95% CI: 0.89-1.00) and 0.82 (95% CI: 0.59-0.97), 0.80 (95% CI: 0.52-0.98), respectively. The pooled sensitivities of 68Ga-FAPI and 18F-FDG PET/CT in lymph nodes or distant metastases were 0.717(95% CI: 0.698-0.735) and 0.525(95% CI: 0.505-0.546), and the pooled specificities were 0.891 (95% CI: 0.858-0.918) and 0.821(95% CI: 0.786-0.853), respectively. Conclusions This meta-analysis concluded that 68Ga-FAPI and 18F-FDG PET/CT had a high overall diagnostic performance in detecting the primary staging and lymph nodes or distant metastases of APMs, but the detection ability of 68Ga-FAPI was significantly higher than that of 18F-FDG. However, the ability of 68Ga-FAPI to diagnose lymph node metastasis is not very satisfactory, and is significantly lower than that of distant metastasis. Systematic review registration https://www.crd.york.ac.uk/prospero/, identifier CRD42022332700.